2012
DOI: 10.1093/jnci/djs346
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Behavioral Risk Factors and Obesity to Socioeconomic Differences in Colorectal Cancer Incidence

Abstract: A substantial proportion of the socioeconomic disparity in risk of new-onset colorectal cancer, and particularly of right colon cancers, may be attributable to the higher prevalence of adverse health behaviors in low-SES populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
2
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(142 citation statements)
references
References 40 publications
(42 reference statements)
5
132
2
3
Order By: Relevance
“…Although smoking was reported as a risk factor for colorectal cancers in several studies (16,18,40), this study showed no significant relationship between smoking and colorectal cancers. Some limitations such as under-reporting of smoking use, different smoking pattern in different region and also small sample size in this study are considered as explanations for this matter.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Although smoking was reported as a risk factor for colorectal cancers in several studies (16,18,40), this study showed no significant relationship between smoking and colorectal cancers. Some limitations such as under-reporting of smoking use, different smoking pattern in different region and also small sample size in this study are considered as explanations for this matter.…”
Section: Discussioncontrasting
confidence: 89%
“…Previous studies have verified the association between some risk factors such as obesity (16) inactivity (16) low socioeconomic status (16,17), smoking (18), some nutritional habits such as carbohydrates, fats, red meat and low fiber use (19,20) with colorectal cancer. Also the effects of alcohol consumption on colorectal cancer have been confirmed by some studies, while other studies have rejected this effect (21).…”
Section: Introductionmentioning
confidence: 96%
“…CRC was more common in higher SEP groups in 21 countries in 1997, which was consistent with our findings with a correlation coefficient of 0.69-0.71. Higher CRC incidence among high SEP group recommended a higher prevalence of risk factor such as smoking in this group in Tehran but in 2012 the overall incidence of CRC after controlling for other risk factors was significantly higher among low educational level or low-SEP groups where prevalence of adverse health behaviors along with BMI explained 36% of the association of local SEP with risk of colorectal cancer (Doubeni et al, 2012a;2012b). Evidence indicates a upward slope between CRC incidence and socioeconomic deprivation in recent decade which SEP pattern in CRC has changed direction (Kee et al, 1996;Pollock and Vickers, 1997;Oliphant et al, 2011).…”
Section: Correlation Of Cancer Incidence With Probable Risk Facmentioning
confidence: 99%
“…CRC is associated with several lifestyle factors, including alcohol consumption, smoking, diabetes and obesity. [37][38][39][40] Recent Hispanic immigrants are less likely to smoke and consume excessive alcohol and are more likely to have healthy dietary habits than US-born Hispanics. 41 However, as Hispanics become more acculturated they become less likely to maintain many aspects of a healthy lifestyle which may offset any improvement from increased screening.…”
Section: Rates Among Hispanics Did Not Decline Until 2008 (Table 2)mentioning
confidence: 99%